Experiences at recovery community centers predict holistic recovery outcomes: a daily diary assessment of RCC helpfulness, meaningfulness, and recovery identity - Hannah B. Apsley; Joseph Lancaster; Wen Ren; Timothy Brick; H. H. Cleveland (Frontiers in Public Health)
IntroductionRecovery community centers (RCCs) offer various support services to people in addiction recovery, such as hosting mutual help meetings and sober social activities and providing employment support and recovery coaching. To date, very little is known about RCCs and their relationship with recovery outcomes, as well as how RCCs may vary in helpfulness from visit to visit. This study used a daily diary approach to assess the intraindividual variation of daily RCC helpfulness, and whether RCC helpfulness predicted the holistic recovery indices of daily meaningfulness and recovery identity.Methods and materialsRCC attendees (analytical N = 88) from RCCs in Pennsylvania completed daily diary assessments using a smartphone application, for 10 consecutive days. If participants reported that they had spent time at the RCC that day, they then reported the perceived helpfulness of the RCC visit using 7 items. Participants also reported their daily meaningfulness and recovery identity. Ultimately, participants visited their RCC on 247/799 (30.9%) of all reported study days. Multilevel models were used to assess the hypotheses.ResultsParticipants generally reported that their RCC visits were very helpful (M = 87.13 [scale of 0–100], SD = 13.26). Nearly half of the variation in RCC helpfulness was attributable to intraindividual variation (ICC = 0.51). Multilevel models revealed that both interindividual and intraindividual RCC experiences predicted increased holistic recovery outcomes, over the prior day. Individuals’ mean levels of perceived RCC helpfulness, as well as person-mean-centered RCC daily helpfulness, positively predicted daily meaningfulness and recovery identity.ConclusionRCCs predict the holistic recovery outcomes of meaningfulness and recovery identity outcomes on the particular days that the RCCs are visited, and for the individuals who find RCCs more helpful overall. This study offers preliminary evidence to suggest that RCCs are appropriate recipients of public funding intended to support recovery in US communities.